COMPETITIVIDAD Y PERCEPCIÓN DEL SERVICIO TURÍSTICO PERUANO ESTUDIO DE INVESTIGACIÓN 2005 - Begazo Villanueva, José Domingo (2007)
Peruvians should look for the wealth inside themselves. We, Peruvians, are full of opportunities, waiting for somebody to give value and the necessary force to transform it into something attractive and powerful to be sold in the world. The key is to understand that we are a nation with a great living culture fruit of centuries of racial mestizaje ; exactly that mestizaje has made our kitchen have a varied and diverse proposals that have captured the international public, and it is in that mestizaje where Peruvians should find not only the source of inspiration to generate wealth but to accept and love themselves as a nation.